Assessment of Training Loads of Highly Qualified Basketball Players - Viktor Koryahin (OVS LLC, 2022)
The purpose of the study is: 1) development and unification of a system of training loads monitoring by the nature of the physiological impact on the basketball players' body; 2) study of the strategy of preparing a highly qualified basketball team for important international competitions, namely: to find out the nature of the distribution of means of different physiological, as well as technical-tactical and game orientation at different stages of preparation; 3) test basketball players before and after training. Materials and methods. A team of highly qualified basketball players (masters of sports and masters of sports of international class) in the number of 15 people participated in the research. The assessment of physical load by the nature of the physiological impact on the body of basketball players during 18 microcycles using 4 - 1 system, that is, 4 working days and 1 day off, was carried out. Athletes were tested before and after training. Results. The dynamics of the means of training by the nature of the physiological impact on the athletes' body have been established. The nature of the distribution of means at different stages of preparation has been established. The test results before and after training are shown. Conclusions. The research results showed that a certain accounting system based on assessments of the nature of the tasks to be solved and the degree of compliance with the specifics of their game activities has developed in basketball. At the same time, research have indicated the need for accounting and analyzing of the training loads by the nature of physiological impact on the body of athletes.